Chromoselective access to Z- or E- allylated amines and heterocycles by a photocatalytic allylation reaction - Ana María Martínez-Gualda; Rafael Cano; Leyre Marzo; Raúl Pérez-Ruiz; Javier Luis-Barrera; Rubén Mas-Ballesté; Alberto Fraile; Víctor A. de la Peña O’Shea; José Alemán (Nature Communications, 2019)
Tsuji–Trost allylation is a traditional method for selective C-C bond formation that involves the use of palladium-based catalysts. Here, the authors report a metal-free, photocatalytic allylation of several heterocycles, amines and alcohols, which can be easily tuned towards the Z- or E- allylated product.